Long‐term glycaemic response and tolerability of dapagliflozin versus a sulphonylurea as add‐on therapy to metformin in patients with type 2 diabetes: 4‐year data. Issue 6 (6th April 2015) - Del Prato, S.; Nauck, M.; Durán‐Garcia, S.; Maffei, L.; Rohwedder, K.; Theuerkauf, A.; Parikh, S.
Abstract : Aims: To assess the long‐term efficacy and tolerability of dapagliflozin versus glipizide as add‐on to metformin in patients with inadequately controlled type 2 diabetes. Methods: The present study was an extension of an earlier randomized, double‐blind, phase III study of dapagliflozin (n = 406) vs glipizide (n = 408) to 208 weeks (4 years). Patients continued to receive their assigned medication. No statistical treatment‐group comparisons were calculated. Results: At 208 weeks, dapagliflozin compared with glipizide produced sustained reductions in glycated haemoglogin (HbA1c): −0.30% [95% confidence interval (CI), −0.51 to −0.09], in total body weight: −4.38 kg (95% CI −5.31 to −3.46) and in systolic blood pressure (SBP): −3.67 mmHg (95% CI −5.92 to −1.41). The HbA1c coefficient of failure was significantly lower for dapagliflozin than for glipizide: 0.19 (95% CI 0.12–0.25) versus 0.61 (95% CI 0.49–0.72, difference −0.42; p = 0.0001). Dapagliflozin was not associated with glomerular function deterioration, while this occurred more frequently in patients in the glipizide group. Fewer patients reported hypoglycaemia in the dapagliflozin compared with the glipizide group (5.4 vs 51.5%). Genital and urinary tract infections were more common with dapagliflozin than with glipizide, but their incidence decreased with time and all events responded well to antimicrobial treatment. Conclusions: In patients completing 4 years of treatment, dapagliflozin was well tolerated and associated with sustained glycaemic efficacy and greater reductions in body weight and SBP versus glipizide.